Relevance of antiphospholipid antibody profile in the clinical outcome of ITP: a single-centre study. Issue 1 (1st January 2019) - Frison, Luca; Lombardi, Annamaria; Caputo, Ilaria; Semenzato, Gianpietro; Fabris, Fabrizio; Vianello, Fabrizio
ABSTRACT: Objectives: The relevance of detecting antibodies against anticardiolipin, β2-glycoprotein I (β2gpI) or lupus anticoagulant (LA), collectively called antiphospholipid autoantibodies (APA), in subjects with immune thrombocytopenia (ITP) is still a debated issue. In particular, whether APA profile may affect the clinical course of ITP is unknown. Methods: In this study, we report our experience in a cohort of ITP patients with APA with specific interest to the relevance of different antiphospholipid antibody profiles in clinical outcome and response to treatment. Results: Thirty-seven out of 159 patients (23.2%) fulfilling ITP criteria had a platelet count ≤50 × 10 9 /L and tested positive at APA at ITP onset. Twenty-three (62.1%) patients received at least one line of treatment for ITP. Fourteen subjects (37.8%) showing triple positivity for APA showed a significantly lower median platelet count compared to other APA patients ( p  = .006). Among these ITP subjects with triple positivity, 85.7% needed a treatment because of low platelet count compared to 47.8% ITP patients with non-triple-positive APA ( p  = .0094). ITP/APA subjects who received immunosuppressors had a higher rate of thrombosis ( p  = .024) as well as thrombosis developed in subjects who were on steroid therapy at a significantly higher dosage than subjects who did not develop thrombotic episodes ( p  < .001). When considering treatment, CR and SR rate were significantly higher in ITP/triple-positive patients compared to non-triple-positive subjects ( p  = .021 and p  = .005). Conclusions: The profile of APA may affect the outcome of patients with ITP.